2020
DOI: 10.1186/s12890-020-1093-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high-flow nasal cannula oxygen therapy on exercise capacity in fibrotic interstitial lung disease: a proof-of-concept randomized controlled crossover trial

Abstract: Background: Patients with fibrotic interstitial lung disease (FILD) often experience gas exchange abnormalities and ventilatory limitations, resulting in reduced exercise capacity. High-flow nasal cannula (HFNC) oxygen therapy is a novel treatment, whose physiological beneficial effects have been demonstrated in various clinical settings. We hypothesized that HFNC oxygen therapy might be superior to conventional oxygen therapy for improving exercise capacity in FILD patients. Methods: We performed a prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 39 publications
2
30
2
1
Order By: Relevance
“…Moreover, in subjects with stable COPD and severe ventilatory limitation for instance, the use of HFNC can better improve endurance time and blood oxygen saturation during exercise than SOT [ 14 ]. In contrast, these higher benefits did not appear to be present in a previous study that compared HFNC and SOT in an heterogeneous group that included different interstitial lung diseases [ 15 ]. However, there is a complete lack of previous studies assessing the potential advantages of HFNC in IPF in particular.…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…Moreover, in subjects with stable COPD and severe ventilatory limitation for instance, the use of HFNC can better improve endurance time and blood oxygen saturation during exercise than SOT [ 14 ]. In contrast, these higher benefits did not appear to be present in a previous study that compared HFNC and SOT in an heterogeneous group that included different interstitial lung diseases [ 15 ]. However, there is a complete lack of previous studies assessing the potential advantages of HFNC in IPF in particular.…”
Section: Introductionmentioning
confidence: 66%
“…There is only one previous paper, published by Suzuki et al, that approximates the usefulness of HFNC in ILD patients during exercise [ 15 ]. They also performed a randomized crossover study using HFNC versus SOT in a mixed pool of different fibrotic ILD patients who have in common that they reached a very low SpO 2 (< 88%) during an incremental CPET.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is expected that these effects are useful for preventing severe EIH and reducing the effort of breathing during exercise (Fig. 3) Cirio et al 31) have evaluated the effects of the administration of oxygen using HFNC in patients with COPD during exercise and reported that EIH and dyspnea were sig- nificantly reduced and oxygen therapy using HFNC allowed the patients to exercise for a longer time with a higher exercise intensity A randomized controlled crossover trial 32 ) was conducted to compare the effects of HFNC (50 L/min; FIO2 0.5) on exercise endurance time, SpO2, and dyspnea with those of oxygen therapy using a Venturi mask (15 L/min; FIO2 0.5) in patients with fibrotic ILD. They reported no significant differences in endurance time, SpO2, and dyspnea between HFNC and Venturi mask.…”
Section: ) High-flow Nasal Cannula Oxygen Therapymentioning
confidence: 99%